Social Acceptance and Self-Confidence of Inclusive Students In State Junior High School in Padang City - Ramadhan, Naufal Fawwaz; Taufik, Taufik (Universitas Negeri Padang, 2025)
Study This against the background existence phenomenon in junior high school where student inclusion Still face obstacle social , especially in matter reception from environment surrounding area , low reception social the can impact on trust self students , so that bother development social and emotional they . Trust less self can also hinder participation active student in activity learning and interaction social. Research This aim For describe reception social and trust self-student inclusion in a number of public junior high schools in Padang City. Research This use method study quantitative with type study descriptive . The sample uses technique cluster sampling so that get amount sample as many as 62 students . Data obtained using instruments in the form of questionnaire acceptance social and trust self . Research results shows 1) average score reception social 85.10 (65.46%) students are in the category moderate , 2) average score trust self 84.66 (70.55%) students are in the category tall.